The Process Time and Electronic Process - Pegoraro Junior, Paulo Roberto (2016)
The increasingly important role of the electronic process as technical means of adjudication must be understood from the dimension related to the process time and its forms of action. From the analysis of the process steps, we can understand how the principles of the speed and effectiveness are or not affected by the virtualization of procedural acts, especially taking into account the innovations of the draft of the new Civil Procedure Code. Apart from this, one cannot ignore the economic bias imposed by temporal compression and by the demands of immediacy of adjudication, significantly affecting the quality of the process time.